Consideraciones Periodontales en Dientes Incluidos Programados para Tratamiento Ortodóntico - Grados Pomarino, Sixto (2003)
Impacted teeth are common and are often treated with orthodontic eruption, but unwanted periodontal problems can start with the treatment. The present article develops the principal periodontal considerations to know during orthodontic treatment and we report two clinical cases where the maxillary canines get an adequate amount of keratinized tissue following these concerns, preventing at this way the subsequent periodontal alterations.